They're OK. It's us that scares us: a critical analysis of discourse of resistance in Iran - Dehghan, Ehsan; Mohamad Ali, Afida (2015)
Iran has historically had a unique position among other Middle Eastern countries. The people-government gap in Iran is one of the deepest of its kind. Further, it is one of the few countries in the world with laws of compulsory hijab for all women, Muslim or non-Muslim. In recent years, with the rise in popularity of social networking websites, such as Facebook, Iranian women have found a new ground to voice their experiences, protest, and resist against such laws. This study, employing Critical Discourse Analysis, is an attempt to analyze the linguistic features, discursive strategies, and underlying ideologies of this online resistance movement. The corpus under study consists of texts posted by Iranian women on Facebook pages created for this cause, in which women post their experiences with compulsory hijab and its enforcement in Iran in their native language, Persian/Farsi. The Discourse-Historical Approach to Critical Discourse Analysis is the methodology of choice for the present study. Two significant features reveal themselves from the analysis of these texts; 1) that there is a strong dichotomization between Self/Us and Others/Them in the given discourse, and 2)that in contrast to many other studies, Xenophobia is not a feature of this discourse. In contrast, our findings point strikingly to Xenophilia, and what we refer to Oikophobia, or fear of people from one’s own country/culture. On a theoretical level, the findings also point to linguistic considerations researchers need to account for when employing CDA studies on languages other than English.